Dyspepsia Advances in Understanding and Management - Shaffer, Eldon; Curley, Michael (IntechOpen, 2013)
This textbook is specifically written for clinicians involved in managing patients with dyspepsia. It is a practical guide with up-to-date suggestions on evaluation, diagnosis, and management from experts from around the world. Each chapter is a succinct review of current topics that play a role in the pathogenesis and management of this disorder. Special populations such as pediatrics, those with cardiovascular disease and womens health are specifically examined.